2000
DOI: 10.1006/jmre.1999.1944
|View full text |Cite
|
Sign up to set email alerts
|

Dead-Time Free Measurement of Dipole–Dipole Interactions between Electron Spins

Abstract: A four-pulse version of the pulse double electron-electron resonance (DEER) experiment is presented, which is designed for the determination of interradical distances on a nanoscopic length-scale. With the new pulse sequence electron-electron couplings can be studied without dead-time artifacts, so that even broad distributions of electron-electron distances can be characterized. A version of the experiment that uses a pulse train in the detection period exhibits improved signal-to-noise ratio. Tests on two ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
455
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 962 publications
(479 citation statements)
references
References 29 publications
3
455
0
2
Order By: Relevance
“…Pulsed EPR data were recorded on an ELEXSYS E580 EPR spectrometer (Bruker) equipped with a PELDOR unit (E580-400U, Bruker), a continuous-flow helium cryostat (CF935, Oxford Instruments), and a temperature control system (ITC 502, Oxford Instruments). Experiments were performed at Q-band frequencies (33.7 GHz) using an ELEXSYS SuperQ-FT accessory unit and a Bruker AmpQ 10 W amplifier with a Bruker EN5107D2 cavity at 10 K. For PELDOR experiments, the dead-time free four-pulse sequence with phasecycled p/2-pulse was used (Pannier et al 2000). Pulse lengths were optimized to 16 ns (p/2 and p) for the observer pulses and 8 ns (p) for the pump pulse.…”
Section: Nmr Experimentsmentioning
confidence: 99%
“…Pulsed EPR data were recorded on an ELEXSYS E580 EPR spectrometer (Bruker) equipped with a PELDOR unit (E580-400U, Bruker), a continuous-flow helium cryostat (CF935, Oxford Instruments), and a temperature control system (ITC 502, Oxford Instruments). Experiments were performed at Q-band frequencies (33.7 GHz) using an ELEXSYS SuperQ-FT accessory unit and a Bruker AmpQ 10 W amplifier with a Bruker EN5107D2 cavity at 10 K. For PELDOR experiments, the dead-time free four-pulse sequence with phasecycled p/2-pulse was used (Pannier et al 2000). Pulse lengths were optimized to 16 ns (p/2 and p) for the observer pulses and 8 ns (p) for the pump pulse.…”
Section: Nmr Experimentsmentioning
confidence: 99%
“…The 4‐pulse PELDOR experiment is mostly used for distance measurements 8. Briefly, one set of spins (A‐spins) is probed by a detection pulse sequence while the dipolar coupling is selectively introduced by inverting a second set of spins (B‐spins) with a pump pulse (usually placed on the most intense feature of the spectrum).…”
mentioning
confidence: 99%
“…Recently,A rdavan et al have shown using double electronelectron resonance (DEER) spectroscopy that the interaction between electron spins in {Cr 7 Ni}r ings can be controlled to fall within the range needed for two qubit gates.[3] These studies were performed on dimers of {Cr 7 Ni}rings [4] where the S = 1/2 spins in each half are identical.Systems containing different spins also have great potential for QIP as there is then the possibility of manipulating each spin separately.T his underpins the g-engineering idea proposed by Takui and co-workers for organic radicals [5] and work employing heterometallic lanthanide dimers.[6] Large differences in g-values could also be used as am eans to implement entangling two qubit gates.[7] Quantifying weak interactions between very different spins is challenging.I n cases where the interaction can easily be measured, for example by magnetometry or continuous-wave (CW) electron paramagnetic resonance (EPR) spectroscopy, [8] the interaction will be too large to permit implementation of both one-and two-qubit gates in the same molecule.[3] CW EPR spectroscopy can still be au seful tool to investigate dipolar interactions;byobserving the line broadening of aN triplet in at wo-qubit structure,Z hou et al showed the existence of ad ipolar interaction that they could estimate in conjunction with spin density calculations.[9] On the other hand, DEER spectroscopy, [10] while ap owerful tool to measure weak interactions by directly manipulating two weakly interacting spins with specific microwave pulses,i s limited as the bandwidth of the microwave source must encompass the resonant frequency of both electron spins.Here we report at wo-qubit assembly comprising an organic radical within the thread of ah ybrid [2]rotaxane containing a{Cr 7 Ni}ring:this is aheterospin system where the constituent spins possess vastly different g-values.T oquantify the weak interaction between the spins we use "Relaxation Induced Dipolar Modulation" (RIDME) spectroscopy, [11] which has been developed in structural biology to measure distances between dissimilar spins. [12] To make the [2]rotaxane an organic thread was synthesized containing as econdary amine and terminating in an aldehyde (see the Supporting Information for details).…”
mentioning
confidence: 99%
“…[9] On the other hand, DEER spectroscopy, [10] while ap owerful tool to measure weak interactions by directly manipulating two weakly interacting spins with specific microwave pulses,i s limited as the bandwidth of the microwave source must encompass the resonant frequency of both electron spins.…”
mentioning
confidence: 99%
See 1 more Smart Citation